Galectin‐9 activates platelet ITAM receptors glycoprotein VI and C‐type lectin‐like receptor‐2. (6th January 2022) - Zhi, Zhaogong; Jooss, Natalie J.; Sun, Yi; Colicchia, Martina; Slater, Alexandre; Moran, Luis A.; Cheung, Hilaire Yam Fung; Di, Ying; Rayes, Julie; Poulter, Natalie S.; Watson, Steve P.; Iqbal, Asif J.
Abstract: Background: Platelets are multifunctional cellular mediators in many physiological and pathophysiological processes such as thrombosis, angiogenesis, and inflammation. Several members of galectins, a family of carbohydrate‐binding proteins with a broad range of immunomodulatory actions, have been reported to activate platelets. Objective: In this study, we investigated the role of galectin‐9 (Gal‐9) as a novel ligand for platelet glycoprotein VI (GPVI) and C‐type lectin‐like receptor 2 (CLEC‐2). Methods: Platelet spreading, aggregation, and P‐selectin expression in response to Gal‐9 were measured in washed platelet suspensions via static adhesion assay, light transmission aggregometry, and flow cytometry, respectively. Solid‐phase binding assay and protein phosphorylation studies were utilized to validate the interaction between Gal‐9 and GPVI, and immunoprecipitation for detecting CLEC‐2 phosphorylation. Wild‐type (WT), GPVI‐knockout ( Gp6 −/− ), and GPVI and CLEC‐2‐double knockout ( Gp6 −/− / Gp1ba ‐ Cre ‐ Clec1b fl / fl ) mice were used. Results: We have shown that recombinant Gal‐9 stimulates aggregation in human and mouse washed platelets dose‐dependently. Platelets from both species adhere and spread on immobilized Gal‐9 and express P‐selectin. Gal‐9 competitively inhibited the binding of human recombinant D1 and D2 domains of GPVI to collagen. Gal‐9 stimulated tyrosine phosphorylation of CLEC‐2 and proteins known to lie downstream of GPVI and CLEC‐2 including spleen tyrosine kinase and linker of activated T cells in human platelets. GPVI‐deficient murine platelets exhibited significantly impaired aggregation in response to Gal‐9, which was further abrogated in GPVI and CLEC‐2‐double‐deficient platelets. Conclusions: We have identified Gal‐9 as a novel platelet agonist that induces activation through interaction with GPVI and CLEC‐2.